Primigravida Readiness in Facing Childbirth - Rianti, Emy; Masita, Masita; Karma, Agusni; Wasnidar, Wasnidar (Health Notions, 2018)
Maternal readiness will affect labor especially in primigravida. Therefore midwives are required to provide antenatal care and provide information and knowledge about pregnancy, childbirth and postpartum in antenatal visits. The purpose of this study was to determine the readiness of primigravida in facing childbirth and its influencing factors. The research method is cross sectional with quantitative approach. The study sample was 108 primigravida, which was examined pregnancy at Jagakarsa public health center, South Jakarta. Data were collected by questionnaire. Data analysis consisted of univariate analysis, bivariate using chi-square, and multivariate using logistic regression. The results of the study showed that found primigravida mothers who are not ready in the face of childbirth. Anxiety, husband support, knowledge and education are the successive factors associated with the readiness of maternal primigravida in the face of labor. While age, occupation and cost have no significant relationship. The conclusion of this study is that education, knowledge, husband support and anxiety are factors related to primigravida readiness in facing childbirth in Jagakarsa public health center, South Jakarta. Keywords: Readiness, Primigravida, Childbirth